Istratijiyat ta’allum al-qawa’ed al-nahwiyah lada tolabah al-bakalurius bi jami’ah Indonesia - Chik, Abdul Rahman; Jakfar Nasruddin, Rozana (KIRKHS, IIUM, 2020)
Strategies of learning Arabic syntax used by majoring students of Arabic at University of Indonesia (UI)